Correlation Between the Wechsler Adult Intelligence Scale- 3rd Edition Metrics and Brain Structure in Healthy Individuals: A Whole-Brain Magnetic Resonance Imaging Study - Hidese, Shinsuke; Ota, Miho; Matsuo, Junko; Ishida, Ikki; Hiraishi, Moeko; Yokota, Yuuki; Hattori, Kotaro; Yomogida, Yukihito; Kunugi, Hiroshi (Frontiers in Human Neuroscience, 2020)
Background: The Wechsler Adult Intelligence Scale, 3rd edition (WAIS-III) is widely used to evaluate the intelligence quotient (IQ). We aimed to investigate the correlation between the WAIS-III metrics and whole-brain structures using magnetic resonance imaging. Methods: The participants were 266 healthy, right-handed individuals (age: 45.6 ± 12.9 years, 98 males and 168 females). IQs were evaluated using the WAIS-III and Japanese Adult Reading Test (JART). Voxel-based morphometry and diffusion tensor imaging were performed to analyze the correlation of the WAIS-III metrics and JART score with the gray matter volume and white matter integrity, respectively. Results: The verbal IQ significantly and positively correlated with the left gyrus rectus and anterior cingulate gyrus, left posterior insula and planum polare, and left superior and middle frontal gyri volumes (p < 0.05, corrected). The verbal comprehension group index significantly and positively correlated with the left superior and middle frontal gyri, left gyrus rectus and anterior cingulate gyrus, and left middle frontal gyrus volumes and bilateral various regional white matter fractional anisotropy values, respectively (p < 0.05, corrected). In contrast, the JART score showed no correlation with any brain structure. Conclusion: These results suggested the neurostructural bases of the WAIS-III IQs and group indices in the brain of healthy individuals.